Ontogenetic shifts in Symbiodiniaceae assemblages within cultured Acropora humilis across hatchery rearing and post-transplantation phases - Jandang, Suppakarn; Viyakarn, Voranop; Yoshioka, Yuki; Shinzato, Chuya; Chavanich, Suchana (Frontiers in Marine Science, 2024)
Coral reefs have been declining worldwide due to multiple threats. Various approaches for coral restoration have been employed to increase coral populations. Sexual propagation is a crucial technique that can enhance the genetic diversity of coral offspring, thereby increasing coral reef resilience in the face of a changing environment. However, the effectiveness of using sexually reared corals for transplantation depends on many factors, including the biological traits of the coral and the physical environment. This study investigated the relationship between Acropora humilis and Symbiodiniaceae during the ontogenetic stages of the coral in ex-situ conditions and after transplantation to a natural reef. Coral sexual propagation techniques were conducted to produce experimental coral colonies. The fertilization rates of coral gametes averaged 98.48 ± 0.34%. However, the survival rate of juvenile corals gradually declined to 45.96 ± 1.31% at 18 months old under hatchery conditions and to 20% after transplantation to a natural reef. Acropora humilis associated with Symbiodiniaceae lineages belonging to three genera: Symbiodinium, Cladocopium, and Durusdinium. Reared juvenile corals developed a more specific and stable association with particular Symbiodiniaceae under hatchery conditions, whereas after transplantation, corals tended to contain a higher diversity of Symbiodiniaceae lineages. These results indicate that a shift in Symbiodiniaceae composition can provide long-term benefits to corals during their ontogenetic cycle and when the environment changes.